Encounterism : the neglected joys of being in person - Field, Andy (Artist) (W.W. Norton & Company, 2023)
"The light touch of a hairdresser's hands on one's scalp, the euphoric energy of a nightclub, huddling with strangers under a shelter in the rain, a spontaneous snowball fight in the street, a daily interaction with a homeless man--such mundane connections, when we closely inhabit the same space, and touch or are touched by others, were nearly lost to "social distancing." Will we ever again shake hands without a thought? In this deeply rewarding book, Andy Field brings together history, science, psychology, queer theory, and pop culture with his love of urban life and his own experiences--both as a city-dweller and as a performance artist--to forge creative connections: walking hand-in-hand with strangers, knocking on doors, staging encounters in parked cars. In considering twelve different kinds of encounters, from car rides to video calls to dog-walker chats in the park, Field argues "that in the spontaneity and joy of our meetings with each other, we might find the faint outline of a better future""--Provided by publisher.